EFEK SENAM TAI CHI TERHADAP KADAR TRIGLISERID DAN LINGKAR PINGGANG PADA WANITA PASCA MENOPAUSE DI DESA TRIHANGGO KECAMATAN GAMPING - Anida Anida (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2016)
ABSTRACTBackground : metabolic syndrome  is the risk factors of cardiovascular diseases the main death  cause in the world for woman. Decrease of estrogen level in pascamenopause woman can disturb  lipid distribution, then lipid in abdomen will saved.  Increased abdomen lipid caused increased body weight specially abdomen obesitas, trygliseride level and waist circumference.Objective : This research aims to learn the effects of Tai Chi exercise towards atherosclerosis risk parameters metabolic syndrome post menopause women. Method : This is a quasi-experimental research with pretest-posttest control group design. Research subjects were post menopause women aged 54-65 years old and were divided into 2 groups. Treatment group which conducted Tai Chi exercise without music  for 8 weeks, three times per weeks, for 40 minutes. The difference of variable alteration between groups was analyzed by using unpair T-test.Results : Tai Chi exercise showed a level of trygliserida level and  decrease waist circumference, the result of T-test analysis showed p value < 0.05 . Conclusion : befor and after Tai Chi showed not difference between trygliseride level and waist circumference.